DESIGN-FOR-COST-AND-ENVIRONMENT: ONTOLOGICAL ANALYSIS AND COMPARISON OF SERVICE REPRESENTATION APPROACHES. (May 2020) - Villanueva, M.; Yannou, B.; Leroy, Y.; Cluzel, F.; Vautier, M.; Vaija, S.
Abstract: Brought by the need for competent approaches to assess the financial cost and environmental impact towards service design-for-cost-and-environment, this paper investigates on the following service representation approaches: Service Blueprinting, Process Chain Network, Business Process Model & Notation, and Customer Journey Mapping. An ontological analysis further compares their similarities and differences. Lastly, a table summarizes the findings, were further insights could be drawn to help service companies be more aware of both their spending and ecological responsibility.